(untitled) (Global Journal of Medical Research, 2016)
This study has used mainly primary data and information collected from the survey of 300 floating population with the help of an interview schedule through quota-sampling technique has also been used in this study. To have performed the analysis Multiple Binary Logistic Regression Models along with as usual descriptive statistical tools and techniques have been applied in the study. The study revealed that 92 percent floating respondents had heard the name of HIV/AIDS but 52 percent floating respondents did not know the fearfulness of HIV/AIDS. TV (29%) was the most dominate source of hearing about HIV/AIDS. Respondents also knew that using condom during intercourse was only the safety way to avoid HIV/AIDS. It was expected that the result of this study will play a vital role to reassess the national population policy in line with the prevention of HIV/AIDS in Bangladesh and will help policy makers to formulate better policies in order to fight against the current situation. However, there was a real need for more and more studies on this regards. Thus, necessary action was to be taken to reduce the level of HIV/AIDS in the country in order to achieve better living conditions in future.